Integrating education and conservation: a case study of the Huaper wetland - Cardenas Morales, Bruno Kadafi; Oré Gálvez, Saríah Fanny; Castro Aponte, Walter Victor; Aguilar Ozejo, Antony; Ñaupari Molina, Rubén; Huayhua Lévano, Fernando Gari; Mendoza Colos, Manuel (Frontiers in Psychology, 2025)
Wetlands provide essential ecosystem services such as biodiversity conservation, water regulation, and agricultural support. However, in Peru, wetland degradation due to urbanization and unsustainable practices threatens these vital functions. This study applies an experiential environmental education approach to wetland conservation, using the Huaper Wetland as a case study. The research is grounded in constructivist learning theories and evaluates the wetland’s biophysical condition while implementing hands-on educational activities to promote student engagement and community participation. Findings indicate that immersive learning experiences enhance ecological understanding and encourage sustainable behaviors. Additionally, the study identifies key factors influencing the effectiveness of educational interventions in wetland conservation. The research proposes four actionable conservation strategies that align educational efforts with community priorities. The study highlights experiential education as both a conservation tool and a means of transformative learning, offering a replicable model for sustainable wetland management.